The concept of developing competences system in the field of suistanble development - Rakhmangulov, Aleksandr N.; Orekhova, Natalya N.; Osintsev, Nikita A. (Journal of the Belarusian State University. Ecology, 2018)
The original approach is proposed to addressing the problem of realizing the concept of sustainable development based on forming the systemic view in humans on the human environment and its impact on nature during anthropogenic activities. The mechanism for implementation management decisions on implementing the concept of sustainable development based on logistics approach and to ensure a balance of interests and goals in the system «human – society – nature» is presented. It’s shown, how the application of logistics approach and consideration of sustainable development approach as the complex dynamic system allow for the identification of critical contradictions between different aspects of sustainable development for subsequent development of methods of its elimination. The basis of developed concept in the present paper consists of the formulated principles and the logistic model of sustainable development, a mechanism for implementation management decisions and methods of forming the competent approach to the study. The application of proposed concept as the basis for establishing distance courses of advanced training for teachers at all levels of education in order to form the competencies in students in the field of sustainable development.
Keywords: ecology; ecological education; concept; sustainable development; professional development; teachers; schools; colleges; students; logistics; model; competences